CIGB-300-Regulated Proteome Reveals Common and Tailored Response Patterns of AML Cells to CK2 Inhibition - Rosales, Mauro; Rodríguez-Ulloa, Arielis; Pérez, George V.; Besada, Vladimir; Soto, Thalia; Ramos, Yassel; González, Luis J.; Zettl, Katharina; Wiśniewski, Jacek R.; Yang, Ke; Perera, Yasser; Perea, Silvio E. (Frontiers in Molecular Biosciences, 2022)
Protein kinase CK2 is a highly pleiotropic and ubiquitously expressed Ser/Thr kinase with instrumental roles in normal and pathological states, including neoplastic phenotype in solid tumor and hematological malignancies. In line with previous reports, CK2 has been suggested as an attractive prognostic marker and molecular target in acute myeloid leukemia (AML), a blood malignant disorder that remains as unmet medical need. Accordingly, this work investigates the complex landscape of molecular and cellular perturbations supporting the antileukemic effect exerted by CK2 inhibition in AML cells. To identify and functionally characterize the proteomic profile differentially modulated by the CK2 peptide-based inhibitor CIGB-300, we carried out LC-MS/MS and bioinformatic analysis in human cell lines representing two differentiation stages and major AML subtypes. Using this approach, 109 and 129 proteins were identified as significantly modulated in HL-60 and OCI-AML3 cells, respectively. In both proteomic profiles proteins related to apoptotic cell death, cell cycle progression, and transcriptional/translational processes appeared represented, in agreement with previous results showing the impact of CIGB-300 in AML cells proliferation and viability. Of note, a group of proteins involved in intracellular redox homeostasis were specifically identified in HL-60 cells regulated proteome, and flow cytometric analysis also confirmed a differential effect of CIGB-300 over reactive oxygen species (ROS) production in AML cells. Thus, oxidative stress might play a relevant role on CIGB-300-induced apoptosis in HL-60 but not in OCI-AML3 cells. Importantly, these findings provide first-hand insights concerning the CIGB-300 antileukemic effect, and draw attention to the existence of both common and tailored response patterns triggered by CK2 inhibition in different AML backgrounds, a phenomenon of particular relevance with regard to the pharmacologic blockade of CK2 and personalized medicine.